2020
DOI: 10.7554/elife.53470
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural organization of human insula is linked to its macrofunctional circuitry and predicts cognitive control

Abstract: The human insular cortex is a heterogeneous brain structure which plays an integrative role in guiding behavior. The cytoarchitectonic organization of the human insula has been investigated over the last century using postmortem brains but there has been little progress in noninvasive in vivo mapping of its microstructure and large-scale functional circuitry. Quantitative modeling of multi-shell diffusion MRI data from 413 participants revealed that human insula microstructure differs significantly across subd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 86 publications
3
30
0
Order By: Relevance
“…The functional and structural correspondence of the insular subregions is imperative for understanding the diverse functions and relations it has with whole-brain networks. There is a wide array of both structural (25,26) and functional (11,27) profiles, providing insight into the connectivity of the distinct regions shown in the present study. The insular subregions are consistent with that in previous functional (28) and meta-analytical ( 23) studies.…”
Section: Discussionmentioning
confidence: 80%
“…The functional and structural correspondence of the insular subregions is imperative for understanding the diverse functions and relations it has with whole-brain networks. There is a wide array of both structural (25,26) and functional (11,27) profiles, providing insight into the connectivity of the distinct regions shown in the present study. The insular subregions are consistent with that in previous functional (28) and meta-analytical ( 23) studies.…”
Section: Discussionmentioning
confidence: 80%
“…5,22 Additionally, the trajectories were planned tangential to the insular cortex to cover the ventrodorsal functional circuits as well. 4,6,42,43 1) The rostroventral agranular cortex connected to the gyral portion of the anterior cingulate cortex as well as the entorhinal cortex. 2) The intermediate dysganular areas connected to the primary somatosensory cortex, the amygdaloid body, and frontal operculum.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological markers of frustrative events may thus be characterized by interaction between these 3 subsystems. Evidence from structural and functional connectivity studies suggests that the ventral part of the anterior insula demonstrate close connections with the VS, amygdala and hypothalamus and dmPFC (to a lesser extent), whereas the dorsal part is rather connected with frontal pole, dACC and the aMCC/pre-SMA, which are subserving cognitive control processes (Deen, Pitskel, & Pelphrey, 2011; Ghaziri et al, 2018; Menon et al, 2020; Nomi et al, 2016). Indeed, the IMAGEN Consortium (n=1510) has shown that when rewards were unexpectedly omitted, the ventral striatum was negatively correlated with activity of the insular cortex (bilaterally), the aMCC/pre-SMA and the thalamus (Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%